Determination of C-13 CSA tensors: extension of the model-independent approach to an RNA kissing complex undergoing anisotropic rotational diffusion in solution - Ravindranathan, S; Kim, CH; Bodenhausen, G (Journal of Biomolecular NMR, 2005)
Chemical shift anisotropy (CSA) tensor parameters have been determined for the protonated carbons of the purine bases in an RNA kissing complex in solution by extending the model-independent approach [Fushman, D., Cowburn, D. (1998) J. Am. Chem. Soc. 120, 7109-7110]. A strategy for determining CSA tensor parameters of heteronuclei in isolated X-H two-spin systems (X = C-13 or N-15) in molecules undergoing anisotropic rotational diffusion is presented. The original method relies on the fact that the ratio kappa(2)=R-2(auto)/R-2(cross) of the transverse auto- and cross-correlated relaxation rates involving the X CSA and the X-H dipolar interaction is independent of parameters related to molecular motion, provided rotational diffusion is isotropic. However, if the overall motion is anisotropic kappa(2) depends on the anisotropy D parallel to/D-perpendicular to of rotational diffusion. In this paper, the field dependence of both kappa(2) and its longitudinal counterpart kappa(1)=R-1(auto)/R-1(cross) are determined. For anisotropic rotational diffusion, our calculations show that the average kappa(av) = 1/2 (kappa(1)+kappa(2)), of the ratios is largely independent of the anisotropy parameter D parallel to/D-perpendicular to. The field dependence of the average ratio kappa(av) may thus be utilized to determine CSA tensor parameters by a generalized model-independent approach in the case of molecules with an overall motion described by an axially symmetric rotational diffusion tensor.
Keywords: anisotropic rotational diffusion; chemical shift anisotropy tensors; cross-correlation; model-independent approach; NMR